2004
DOI: 10.1021/jp037437o
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Coherent Domain Structure in a Series of π-Conjugated Dendrimers by Simultaneous Three-Photon Absorption

Abstract: We study three-photon absorption (3PA) in a series of 4,4′-bis(diphenylamino) stilbene-based dendrimers and show that the cross section of the nonlinear absorption scales faster than in a linear fashion with the molecular size, which is a manifestation of the cooperative enhancement effect. The coherent domain structure is deduced from 3PA cross section values for all of the dendrimers in the series. It is found that, in terms of largest coherence domain size, the optimum dendrimer generation is 4-arm G-0. Mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 31 publications
3
31
1
Order By: Relevance
“…It has been observed that the molecular nonlinear-optical response of branched molecules and dendrimers may increase faster than the number of their constituent subunits, which is an indication of cooperative enhancement [31][32][33][34][35][36][37]. However, the actual scaling of nonlinear absorption with dendrimer size (generation) was not systematically studied.…”
Section: Introductionmentioning
confidence: 96%
“…It has been observed that the molecular nonlinear-optical response of branched molecules and dendrimers may increase faster than the number of their constituent subunits, which is an indication of cooperative enhancement [31][32][33][34][35][36][37]. However, the actual scaling of nonlinear absorption with dendrimer size (generation) was not systematically studied.…”
Section: Introductionmentioning
confidence: 96%
“…It has been found that there would be additional cooperative enhancement of MPA cross-section in the branched molecules when compared with their constituent subunits. [59,62,63,115,116] Due to Figure 5. Structures of the model systems for a dipolar chromophore (4-dimethylamino-4 0 -cyano-E-stilbene), 9, and a quadrupolar chromophore (4,4 0 -bis(dimethyl)amino-a,b-dicyano-E-stilbene), 10, together with an illustration of the system of point charges used to continuously vary the ground-state polarization.…”
Section: Molecular Dimensionalitymentioning
confidence: 96%
“…[41,54,55] The increase of molecular dimensionality may also enlarge MPA crosssections. [59,[62][63][64] This paper is organized as following. We first describe the theoretical methodologies for MPA response and then we give a detailed discussion about the influences of molecularly intrinsic structure parameters, such as donor/acceptor substitution, p-conjugation length, molecular polarization and dimensionalities on the MPA properties, as well as some other factors, such as vibronic coupling and intermolecular interaction effects.…”
Section: Introductionmentioning
confidence: 99%
“…2, display strong electron delocalization between the branches. The delocalization leads to enhancement of the electronic transition dipole moments of the dendrimer molecule as compared to the sum of individual chromophores [16]. This, in turn, leads to cooperative enhancement of the nonlinear optical response of both 2PA and 3PA cross-section [13][14][15][16][17][18].…”
Section: Article In Pressmentioning
confidence: 99%
“…In recent years, organic synthesis, assisted by improved understanding of the underlying structure-property relationships, has enabled a variety of new compounds with enhanced nonlinear-optical properties [12][13][14][15][16][17][18]. We have recently synthesized highly soluble dendrimer-like organic chromophores, which maximize the efficiency of multiphoton absorption in near IR range of wavelengths [13,17].…”
Section: Introductionmentioning
confidence: 99%